2022
DOI: 10.3390/ijerph19127328
|View full text |Cite
|
Sign up to set email alerts
|

How Government Size Expansion Can Affect Green Innovation—An Empirical Analysis of Data on Cross-Country Green Patent Filings

Abstract: The expansion of government size will have dual effects on a country’s green innovation. An appropriately sized government size increases marginal productivity and stimulates the development of green innovation by increasing government expenditure. On the contrary, an excessively sized government creates a huge administrative agency, which not only increases the tax burden but also damages social welfare by excessive intervention. Therefore, the effect of government size on green innovation is not linear. In o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 78 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…Thus, these solved the problem of limited construction land and prevented the government from attracting backward industries that could bring rapid profits at a low price. However, due to the uncertainty of the impact of government intervention on environmental quality, the effect of land marketization on EEQ through government intervention did not exist [47]. Therefore, these conclusions proved the existence of Hypotheses 2.1 and 2.3 except for Hypothesis 2.2.…”
Section: Driving Mechanism Analysis Of the Impact Of The Mercocl On Eeqmentioning
confidence: 80%
“…Thus, these solved the problem of limited construction land and prevented the government from attracting backward industries that could bring rapid profits at a low price. However, due to the uncertainty of the impact of government intervention on environmental quality, the effect of land marketization on EEQ through government intervention did not exist [47]. Therefore, these conclusions proved the existence of Hypotheses 2.1 and 2.3 except for Hypothesis 2.2.…”
Section: Driving Mechanism Analysis Of the Impact Of The Mercocl On Eeqmentioning
confidence: 80%
“…Since there is a period of time between the filing and granting of a patent, the number of patent applications is used as a measure of innovation performance. Similarly, the number of green patent applications can be used to measure green innovation performance [54]. Therefore, this article uses the total number of green patent applications of listed artificial intelligence companies to measure corporate green innovation indicators.…”
Section: Definition Of Variablesmentioning
confidence: 99%
“…In our opinion, these disparate results may indicate that production knowledge is indirectly related to purchase intentions for green products. For instance, Wen and Li (2013) found that production knowledge moderated the relationship of risk perceptions with purchase intent for green products. However, whether production knowledge plays a moderating role in influencing green purchase behaviour remains relatively under‐investigated.…”
Section: Hypotheses Developmentmentioning
confidence: 99%